Penggunaan Media Gambar Terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam di SD Negeri 1 Tamanwinangun - Dwinanda Suluh Phangesti; Imam Subarkah; Maryanto Maryanto (Tarbi: Jurnal Ilmiah Mahasiswa, 2023)
The purpose of this study was to determine the use of image media in Islamic Religious Education (PAI) learning for sixth grade students of SD Negeri 1 Tamanwinangun. The method used is a quantitative research approach and the type of research conducted is experimental. The design used was a one-group pretest-posttest. Data collection techniques using pretest-posttest tests, questionnaires, interviews, documentation and observation. Hypothesis testing using paired sample t test. The results showed that the use of image media gave a good impression on students and had a positive effect on student learning in grade VI Islamic Religious Education subjects at SD Negeri 1 Tamanwinangun in the 2021/2022 academic year, in general it could improve student learning outcomes with the following results: (a) The average score of students at the pretest was 6.67 and at the posttest was 8.72 (b) students' learning mastery also increased, at the pretest it was 40.7% to 96.3% at the posttest.